Two new acetylenic compounds from Asparagus officinalis. Issue 4 (2nd April 2016) - Li, Xue-Mei; Cai, Jin-Long; Wang, Wen-Xiang; Ai, Hong-Lian; Mao, Zi-Chao
Abstract : Two new acetylenic compounds, asparoffins A (1 ) and B (2 ), together with two known compounds, nyasol (3 ) and 3″-methoxynyasol (4 ), were isolated from stems of Asparagus officinalis . The structures of two new compounds were elucidated on the basis of detailed spectroscopic analyses (UV, IR, MS, 1D, and 2D NMR). All compounds were evaluated for their cytotoxicities against three human cancer cell lines.